VAT Treatment In Gold And Jewelry Trade: Regulation and Implementation Review - Dewi Lubis, Putri Kemala; Syuriani, Evi; Firmansyah, Deyren; Situmorang, Eva Juli Yanti; Hasibuan, Nur Sakinah (Journal of Management Accounting, Tax and Production, 2025)
This research aims to analyze the treatment of Value Added Tax (VAT) in the gold and jewelry trade as well as business actors' compliance with established tax regulations. Even though Minister of Finance Regulation Number 30/PMK.03/2014 and Law Number 7 of 2021 stipulate the obligation to collect VAT of 11% on sales of gold and jewelry, research results show that the majority of gold shops in Deli Serdang have not implemented this provision. This is caused by a lack of understanding by business actors regarding tax regulations, minimal outreach from the authorities, and concerns that the implementation of VAT will have a negative impact on consumer purchasing power. This research emphasizes the importance of increasing ongoing outreach, supervision and training efforts to encourage compliance by business actors in carrying out tax obligations. The government also needs to balance law enforcement with a supportive approach to maintaining the stability and sustainability of the national jewelry industry.